2017
DOI: 10.1111/cid.12471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different hierarchical hybrid micro/nanostructure surfaces on implant osseointegration

Abstract: These results indicated that HF + MS surfaces exhibited superior material property in terms of bonding strength and favorable implant osseointegration compared to other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The sample size calculation was based on a BIC results of one study that evaluated different micro/nanostructure surfaces on implant osseointegration compared with machined surfaces (Cheng et al, ). This study showed that the smallest difference between the means of the groups where there were statistically significant differences was 18.75% with a standard deviation of 4.24%, it was verified that a sample of seven animals per group/period was sufficient to apply statistical tests with an α‐type error of 0.05 and a β‐power of 0.90.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size calculation was based on a BIC results of one study that evaluated different micro/nanostructure surfaces on implant osseointegration compared with machined surfaces (Cheng et al, ). This study showed that the smallest difference between the means of the groups where there were statistically significant differences was 18.75% with a standard deviation of 4.24%, it was verified that a sample of seven animals per group/period was sufficient to apply statistical tests with an α‐type error of 0.05 and a β‐power of 0.90.…”
Section: Methodsmentioning
confidence: 99%
“…In order to improve the roughness of the surface, many industrial techniques have also been developed to produce a thin coat (sol–gel deposition, sputtering coating techniques, or ion beam-assisted deposition) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Andrukhov [18] reported that a moderately rough surface (Sa = 1-2 µm) had a considerable impact on osteoblast differentiation. Furthermore, hybrid micro/nanostructure implant surfaces have been reported to affect osseointegration through managing cell behaviors; micro-nano hybrid structure surfaces increased the wettability of such implants [19][20][21]. In this study, the Sa values for cpTi, CTO 700, and CTO 800 were relatively smoother than those of the prior reports (0.49 µm, 0.62 µm, and 0.87 µm, respectively).…”
Section: Discussionmentioning
confidence: 50%